RANCANG BANGUN TRANSAKSI RENTAL MOBIL DENGAN TEKNOLOGI WEB PADA ALKO RENT CAR - Rusito Rusito (MANAJEMEN, 2022)
In this modern era, the world of science and technology is growing rapidly. Along with this, the flow of information is also growing and the need for quality information is increasing. CV. ALKO Rent Car is an individual business engaged in services, especially transportation services.The previous rental process only used a borrowing system through advertisements in print media and only by word of mouth. This is of course a bit detrimental to the company, because if there are customers from outside the city who will use the car rental service, they cannot know the types of cars that will be used and the price of the car rental. By using a transaction system with web technology, it ishoped that the company can increase the number of customers and not only from the city of Semarang. In addition, the admin section will not experience difficulties when writing reports or customer data collection, because customer data collection can be done in an easier way by entering the customer member, the admin section will find out whether the customer has used the car rental service or not.With web technologies such as HTML, CSS, PHP and MySQL databases as well as utilizing the internet network, it is hoped that it can solve problems related to customer reach.This study uses the Borg and Gall (1987) model from 10 steps to 6 steps. The expert system validation test shows the final value of the calculation is 2.5, concluding that it is very feasible to use. User Validation on CV. ALKO Rent Car Semarang obtained a value of 3.0 stating that the system is feasible to use and good.